(untitled) (Journal of Asian Development Studies, 2023)
Geospatial positioning of Gilgit-Baltistan exposed the land of the mighty Himalaya-HindukushKarakoram region to adverse impacts of climate change. Climate change is a "Global" issue that calls for "Glocal" action. Deficit and impaired public perceptions of climate change and its imposed risks and adverse impacts could herald climate change adaptation, mitigation, and resilience policies as well as practices at the local level. Climate Change can be evident over decades, and it is often challenging to perceive it in the short run by personal experiences. Adequate public perception and beliefs regarding climate change pave the way for efficient climate change actions. The study explored the role of demographic and socio-economic factors, i.e. age, gender, employment status, education level, and access to information and warning systems, in shaping climate change public perception in mountain communities of Gilgit Baltistan (GB). Survey data were collected using random stratified sampling across the GB overall 892 observations were collected. The Logistic regression analysis results reveal that access to warning systems through mobile phones, formal education, employment, adult people, and male respondents tend to have higher levels of climate change perception and beliefs. The study also found that most respondents have experienced an increase in temperature and a change in precipitation patterns, with increased hazardous incidences such as floods, avalanches, and landslides. The research findings recommend developing an integrated policy framework for local climate actions by strengthening education, disseminating warning systems, and promoting employment opportunities for inclusive climate change adaptation and mitigation practices in the GB.